Peningkatan Kesadaran Remaja tentang Anemia sebagai Upaya Pencegahan Stunting melalui Edukasi di SMAN 1 Baregbeg - Suminar, Ratna; Hindiarti, Yudita Inga; Perdana, Isma Madya (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2025)
Anemia in adolescents, especially girls, is a health problem that has long-term impacts and contributes to the risk of stunting. Lack of knowledge is a major obstacle in preventing it. This community service aims to increase student awareness of anemia through health education. The activity was carried out at SMAN 1 Baregbeg and was attended by 300 students. The method used was interactive counseling with the help of the digital platform Kalkulating (Stunting Detection Calculator) and group discussions. Evaluation was carried out using pretests and posttests. Evaluation was carried out through questionnaire-based pretests and posttests to measure the level of knowledge before and after the intervention. The pretest results showed that 10% of students had good knowledge, 39% sufficient, and 51% lacking. After the counseling, there was a significant increase in student knowledge to 87% good. This activity shows that a digital educational approach can improve adolescents' understanding of the impact of anemia.